Operative Dictations in Plastic and Reconstructive Surgery - Anh Tran, Tuan; Panthaki, Zubin J.; Hoballah, Jamal J.; Thaller, Seth R. (Springer International Publishing : Imprint: Springer, 2017)
This text provides a comprehensive overview of operative dictations in plastic, aesthetic, and reconstructive surgical procedures, which will serve as a valuable resource for residents, fellows, and practicing surgeons. The book provides step-by-step operative details regarding all indexed plastic surgery cases that a resident is expected to be thoroughly acquainted with for his or her daily practice and examinations. Each case is preceded by a list of common indications, covering most of the situations in which particular procedures will be used, as well as a list of essential steps. Operative Dictations in Plastic and Reconstructive Surgery will serve as a very useful resource for physicians dealing with, and interested in the field of plastic surgery. It will also provide the related data for the newly minted practicing plastic surgeons. All chapters are written by authorities in their fields and include the most up-to-date scientific and clinical information. .
Keywords: Medicine.; Rectum -- Surgery.; Surgery.; Plastic surgery.; Vascular surgery.; elektronické knihy; electronic books